Epidemiology of injuries in ice hockey - Anderson, G. R.; Melugin, H. P.; Stuart, M. J. (Sports Health: A Multidisciplinary Approach, 2019)
Context: Hockey is a skillful contact sport with an elevated injury risk at higher levels of play. An understanding of injury incidence, type, mechanism, and severity at various levels of competition aids the clinician treating these athletes. The purpose of this clinical review is to discuss the epidemiology of hockey injuries at various levels of participation, including youth, high school, junior, college, and professional.